2010
DOI: 10.1093/jxb/erq306
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related differences in morphological, physiological, and ultrastructural responses of Populus cathayana to chilling

Abstract: Low temperature is one of the abiotic factors limiting plant growth and productivity. Yet, knowledge about sex-related responses to low temperature is very limited. In our study, the effects of low, non-freezing temperature on morphological, physiological, and ultrastructural traits of leaves in Populus cathayana Rehd. males and females were investigated. The results showed that 4 °C temperature caused a chilling stress, and females suffered from greater negative effects than did males. At the early growth sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
75
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(83 citation statements)
references
References 73 publications
8
75
0
Order By: Relevance
“…Peroxidases are a kind of antioxidant enzymes, which can remove ROS in plant cell (Breusegem et al, 1999). Previous studies mainly focused on SOD, POD and CAT activities, however, due to the material properties and the difference of stress duration and intensity, changes in antioxidant enzymes under low temperature stress were not so regular (Gechev et al, 2003;Zhang et al, 2011;Li et al, 2013). In our experiment, the resistant variety initiated osmotic regulation system firstly and then triggered the antioxidant enzyme system when exposed to low temperature stress for long duration.…”
Section: Discussionmentioning
confidence: 83%
“…Peroxidases are a kind of antioxidant enzymes, which can remove ROS in plant cell (Breusegem et al, 1999). Previous studies mainly focused on SOD, POD and CAT activities, however, due to the material properties and the difference of stress duration and intensity, changes in antioxidant enzymes under low temperature stress were not so regular (Gechev et al, 2003;Zhang et al, 2011;Li et al, 2013). In our experiment, the resistant variety initiated osmotic regulation system firstly and then triggered the antioxidant enzyme system when exposed to low temperature stress for long duration.…”
Section: Discussionmentioning
confidence: 83%
“…As the different reproduction costs, males and females have evolved different adaptive strategies to environmental stresses (Dawson and Bliss, 1989;Dawson and Ehleringer, 1993). Our previous studies have shown that there are different tolerance and sensitivity in male and female poplars to nitrogen deposition, photoperiod, heavy metals, sanity, chilling and rust disease (Zhao et al, 2009(Zhao et al, , 2011Chen et al, 2010a,b;Zhang et al, 2010aZhang et al, , 2011. In these studies, we found a common phenomenon that male poplars showed higher antioxidant enzyme activities than females under the above stresses.…”
Section: Introductionmentioning
confidence: 76%
“…Meanwhile, soil salinization and alkalization frequently co-occur in nature. Although ecophysiological response to environmental change in P. cathayana has been widely measured (Chen et al 2010, Xu et al 2010, Zhang et al 2011, no measurements of g m for P. cathayana have been conducted to our knowledge under alkaline stress. In the present investigation, photosynthesis, g m , PNUE, as well as δ 13 C of P. cathayana were assessed under alkaline stress.…”
Section: ---mentioning
confidence: 99%